DNA-Based Nanobiosensor for the Colorimetric Detection of Dengue Virus Serotype 2 Synthetic Target Oligonucleotide - Michael Sandino C. Flores; Evangelyn C. Alocilja; Divina M. Amalin; Mae Joanne B. Aguila; Marynold V. Purificacion; Florinia E. Merca; Ma. Carmina C. Manuel; Mark Pierre S. Dimamay; Ma. Anita M. Bautista; Lilia M. Fernando (Biosensors)
Annually, the Philippines is burdened by a high number of infections and deaths due to Dengue. This disease is caused by the Dengue virus (DENV) and is transmitted from one human host to another by the female Aedes aegypti mosquito. Being a developing country, most of the high-risk areas in the Philippines are resource-limited and cannot afford equipment for detection and monitoring. Moreover, traditional clinical diagnoses of DENV infection are costly and time-consuming and require expertise. Hence, it is important to establish effective vector control and surveillance measures. In this study, we developed a DNA-based nanobiosensor for the colorimetric detection of Dengue virus serotype 2 (DENV-2) synthetic target DNA (stDNA S2) using gold nanoparticles (AuNPs). We successfully functionalized dextrin-capped gold nanoparticles with the designed DENV-2 oligonucleotide probes. The detection of the complementary stDNA S2, indicated by the pink-colored solution, was successfully performed within 15 min using 0.40 M NaCl solution. We were able to detect up to 36.14 ng/μL of stDNA S2 with some cross-reactivity observed with one non-complementary target. We believe that our study offers a basis for developing nanobiosensors for other DENV serotypes.